Kinetic and metabolic behaviors of aerobic granules developed in sequencing batch reactors - Li, Yong (2009)
The previous research on aerobic granulation was mainly focused on the factors affecting aerobic granulation. However, little has been know about the metabolic behaviors and modeling of aerobic granular sludge process. In this study, a one-dimensional model was developed and successfully applied to aerobic granular sludge SBR. The diffusion profiles of organic substrate and dissolved oxygen in aerobic granules were simulated using the proposed model system under varies conditions. It was found that diffusions of organic substrate and oxygen in aerobic granule would be a dynamic process, and were closely interrelated. Simulation of the overall performance of aerobic granular sludge SBR showed that dissolved oxygen would be a main limiting factor of the metabolic activity of aerobic granules. Smaller aerobic granules exhibited higher metabolic activity in terms of the substrate removal rate. For a SBR dominated by aerobic granules larger than 0.5 mm, dissolved oxygen would be the bottleneck which limits the substrate utilization rate. It is expected that the model system developed in this study can provide an effective and useful tool for predicting and optimizing the performance of aerobic granular sludge reactor.